Bilateral Dysfunction of Otolith Pathway in Patients With Unilateral Idiopathic BPPV Detected by ACS-VEMPs - Niu, Xiaorong; Han, Peng; Duan, Maoli; Chen, Zichen; Hu, Juan; Chen, Yanfei; Xu, Min; Ren, Pengyu; Zhang, Qing (Frontiers in Neurology, 2022)
Objective: To observe the functional status of the otolith pathway in patients with unilateral idiopathic benign paroxysmal positional vertigo (BPPV) by combining air-conducted sound elicited cervical vestibular-evoked myogenic potential (ACS-cVEMP) and ocular vestibular-evoked myogenic potential (ACS-oVEMP). Methods: One hundred and eighty patients with BPPV were recruited for conventional cVEMP and oVEMP tests. The abnormal rates of VEMPs were compared between BPPV patients and control participants. Results: The abnormal rates of cVEMP and oVEMP in BPPV patients were 46.7% (84/180) and 57.2% (103/180) in affected ears, respectively, and 45.0% (81/180) and 56.7% (102/180) in unaffected ears, respectively; both were significantly higher than the abnormal rates of cVEMP and oVEMP in normal control ears. Compared with normal subjects, cVEMP response rate was lower in affected and unaffected ears in BPPV patients. The abnormal rates of cVEMP and oVEMP were 48.1% (76/158) and 57.6% (91/158) in patients with posterior semicircular canal BPPV, and 36.4% (8/22) and 54.5% (12/22) in lateral semicircular canal BPPV. There was no significant difference in VEMP abnormalities between posterior semicircular canal BPPV and lateral semicircular canal BPPV. Conclusion: The prevalence of abnormal cVEMPs and oVEMPs in both affected and unaffected ears of patients with BPPV was significantly higher than that observed in the control group. The pathological mechanism of unilateral idiopathic BPPV may be associated with bilateral degeneration of otolith pathways.